The degree of application of the community school concept and its role in spreading the culture of community participation (Damascus University Journal of arts and humanities sciences, 2024)
The aim of the research is to identify the degree of application of the concept of the community school and its role in spreading the culture of community participation from the point of view of teachers in the city of Tartous. To achieve the goal of the research, the researcher used the descriptive analytical method, and the research sample consisted of (327) male and female teachers in schools in the city of Tartous for the academic year 2023/ 2024, and the tool consisted of a questionnaire about the application of the concept of the community school in the city of Tartous and its role in spreading the culture of community participation, prepared by the researcher, and it included (27) items distributed over two axes: (application of the concept of the community school, the role of the school in spreading the culture of community participation), after verification. From its validity and consistency, the results showed that the degree of application of the concept of community school in the city of Tartous from the teachers’ point of view is average, with an arithmetic mean (3.08) and a standard deviation (.501), and the role of the school in spreading the culture of community participation from the teachers’ point of view is medium, with an arithmetic mean (3.28), and a standard deviation of (.353). The researcher recommended the need to provide guidance and training within educational institutions to develop the skills of their members in enhancing community participation, and the use of technology to enhance community participation, in addition to the need to encourage teachers to communicate continuously and effectively with parents to enhance cooperation and partnership in Supporting community participation.
Keywords: Community School; Community Engagement